GAZA AT THE INTERSECTION OF SOCIAL WORK AND HUMAN RIGHTS - Algan, Taner; Kutlu, Ihsan; Kara, Hüseyin Zahid (My University, 2024)
Social work is a human rights profession and discipline. One of the main objectives of social work is to ensure human rights at a universal level. In this way, it will be possible to secure the rights of people from all walks of life and geographies without discrimination and to increase their living standards. Within the scope of this ideal, social work carries out studies at the theoretical and practical level and puts every event that can be evaluated on the basis of human rights on its agenda. What happened in Gaza after October 7, 2023 has been included in the agenda of social work as one of the most prominent examples of human rights violations. However, states, organizations and disciplines that advocate for human rights in the face of attacks in which tens of thousands of civilians, many of them women and children, have been massacred have failed to have a concrete impact. As a matter of fact, while Israel's attacks on civilians in Gaza continue unabated, it has been observed that the structures that are expected to react to the events have exhibited a passive attitude. This study focuses on the evaluation of the events in Gaza after October 7, 2023 in terms of the profession and discipline of social work. In this context, both the attacks and the current situation were discussed from the perspective of social work and the concrete steps taken by social work in the face of these attacks were examined. As a result of the evaluation, it has been observed that social work has been limited in exhibiting reactions transformed from discourse to action in the face of the attacks in Gaza. In the context of social work, these reactions were expressed only in the form of written statements by IFSW at the international level. In addition, it has been understood that many roles and functions of social work such as advocacy, mediation, activism, community mobilization and anti-oppression have not been effective enough. In this regard, it is stated that it is important for social work to take concrete steps with a realistic, inclusive, fair and mobilizing approach to achieve the ideal of universal human rights.
Keywords: Social Work; Human Rights; Gaza; Social Work Values; Israel Attacks